Identification, Isolation and Culture of 5 Microalgae Isolates From The Sail River, Lima Puluh District, Pekanbaru City - Zikra Yusianda; Efawani Efawani; Kamaruddin Eddiwan (Berkala Perikanan Terubuk, 2022)
Sail River is a sub-watershed of the Siak River in Pekanbaru City with various community domestic activities that cause the waters to be polluted by waste. One of the organisms that is tolerant of poor water quality is microalgae. The aims of this research to determine the potential microalgae in the Sail River. This research was conducted in September-December 2021 using a survey method. There were 4 sampling areas and in each sampling area there were 3 sampling points. Sampling were taken once/week for 3 weeks. Water quality parameters observed were temperature, transparency, pH, DO, CO2, nitrate and phosphate. The microalgae found were then isolated and culture in the laboratory, cultured in water media with Walne fertilizer added and their growth was observed. The results of this study shown that the microalgae found consisted of 2 classes, namely: Chlorophyceae (16 species) and Cyanophyceae (5 species). The isolated microalgae were: Chlorella vulgaris, Coelastrum microporum, Scenedesmus quadricauda, Pediastrum biradiatum and Merismopedia punctata. Microalgae isolates reached peak growth on the 7th to the 8th day. Meanwhile, the harvested biomass ranged from 0,05 g/L to 0,3 g/L. Based on the results of this research, it can be concluded that these five types of microalgae isolates are potential to be utilized.